(untitled) (Fiep Bulletin - online, 2011)
Low back pain is a frequent health problem with approximately 80% of world population suffering or will suffer from the ailment. Aim: to evaluate the influence of manual therapy techniques on life quality in a patient suffering from L5-S1 slipped disc. Methodology: a 28-year-old male patient suffered from severe low back pain and pain spread throughout the gluteal area, at the back of the thigh and left calf. Decreased lumbar mobility in flexion, extension and left side inclination were detected during physiotherapy evaluation, with pain in all his movements. Spasms of the bilateral quadratus lumborum, psoas, piriformis and leftward paravertebral muscles were also perceived. Valsava’s test and Slump’s and Lasegue’s tests were positive for the left lower member. Magnetic resonance reported L5-S1 disc extrusion. Treatment: Life Quality Questionnaire SF-36 was filled by the patient on the first day of treatment and at each four manual therapy session, totally 3 evaluations. Treatment, undertaken once a week, for one hour, totaling eight sessions, consisted of techniques in vertebral mobilization, neural mobilization, muscle lengthening and exercises of low back stabilization. Result: Questionnaire SF-36 comprised an evaluation on eight items: functional capacity, physical aspects, social aspects, emotional aspects, pain, vitality, mental health and general health. The patient improved in all evaluated items. Conclusion: Treatment of low back pain by different manual therapy techniques may be efficient in the improvement of the life quality of patients with L5-S1 slipped disc dysfunctions.